'The Whole Universe is Heterosexual!' Correlates of Homonegativity in seven South-East European Countries - Brajdić Vuković, Marija (Array, 2012)
This paper analyzes micro-determinants of negative attitudes toward homosexuality in seven South-East European societies (Albania, Bosnia and Herzegovina, Croatia, Kosovo, Macedonia, Montenegro, and Serbia). Using data from the South-East European Social Survey, carried out on national probability samples in 2003, we analyzed the individual-level effects of modernization and religious tradition. According to our findings, homonegativity – operationalized as disapproval of homosexuality – was reversely associated with social modernization (education and urbanity). As reported in other similar studies, gender, age, and religiosity were found to have independent effects on homonegativity. Interestingly, persistent religious traditions affected the reported levels of homonegativity differentially – in a country-specific manner. In the pooled sample, Muslim and Orthodox participants were more likely to have homonegative attitudes than Catholic participants, irrespective of their socio-cultural status. When the analysis was carried out separately by country, only age and education were found relatively consistent predictors of attitude toward homosexual individuals. In addition, several country-specific effects were observed, but, overall, the model lacked substantial explanatory power. In conclusion, the authors discuss the role of post-communist transition in generating homonegativity and address possible study limitations.